Polyacrylonitrile-based active carbon fiber as well as preparation method and application thereof

By combining polyacrylonitrile-based activated carbon fiber with MXene material, the problems of excessive pore structure and surface defects in the negative electrode material of sodium ion battery are solved, and the battery rate performance and cycle stability are improved, while reducing production costs.

CN119710986AActive Publication Date: 2025-03-28ZIGONG DONGXIN CARBON CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510005178.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-28
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The existing carbon fibers have problems with cyclic stability caused by excessive pore structure, increased irreversible capacity loss and surface defects in sodium ion battery negative electrode materials, and the stacking and surface energy of MXene materials lead to poor battery rate performance and cycle life.

Method used

Polyacrylonitrile-based activated carbon fiber is combined with MXene material, impurities are removed through pretreatment of phosphoric acid solution and ultrasonic treatment, carbonization is achieved by microwave heating, uniform and complete structure is prepared, and electrochemical performance is regulated by optimizing the material proportion.

Benefits of technology

It effectively improves the layered structural stability of MXene materials, improves the rate performance and cycle stability of sodium ion batteries, reduces production costs, and optimizes electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710986A_ABST
    Figure CN119710986A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of materials, and particularly discloses a polyacrylonitrile-based active carbon fiber and a preparation method and application thereof.The preparation method comprises the steps that polyacrylonitrile is crushed to 140-200 meshes, then immersed in a 5-15 mM phosphoric acid solution and subjected to ultrasonic treatment for 10-20 min, and polyacrylonitrile floccules are obtained; the method comprises the following steps: under the protection of an inert atmosphere, putting polyacrylonitrile floccules into a microwave tube furnace, and activating at a high temperature of 400-600 DEG C for 10-30 minutes; and after the high-temperature activation is finished, carrying out gas bath washing for multiple times, and finally, carrying out vacuum drying to obtain the polyacrylonitrile-based active carbon fiber. The preparation process is simple, the production period is short, the cost is low, the length-diameter ratio of the prepared polyacrylonitrile-based active carbon fiber is equivalent, a trace pore structure is distributed on the surface of the polyacrylonitrile-based active carbon fiber, and the polyacrylonitrile-based active carbon fiber is combined with an MXene material for use, so that the stability of a layered structure of the MXene material can be effectively improved, and the rate capability and the cycling stability of a sodium ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials and relates to carbon fibers, in particular to polyacrylonitrile-based activated carbon fibers and a preparation method and application thereof. Background Art

[0002] Energy issues are one of the major issues facing social development. With the depletion of fossil energy and the gradual deterioration of the environment, people urgently need to develop efficient, clean and sustainable new energy sources and energy storage materials that match them. Activated carbon has a developed pore structure and specific surface area, and is mainly composed of carbon elements. However, the differences in different raw materials often cause activated carbon to contain a small amount of non-carbon elements such as hydrogen, oxygen, nitrogen, etc., and there is a possibility of local segregation, which causes defects in carbon materials. Activated carbon fiber uses organic fiber as a precursor and has excellent acid and alkali resistance, mechanical properties, electrical conductivity and chemical stability. Carbon fiber is less used in the field of energy storage. There are also some disadvantages when it is directly used as a negative electrode material for sodium ion batteries. For example, the pore structure and specific surface area of ​​activated carbon fiber are too large, which may lead to an increase in irreversible capacity loss during the first charge and discharge process and reduce the coulombic efficiency of the battery; on the other hand, the surface defects of activated carbon fiber may become unstable sites during the sodium ion deintercalation process, affecting the cycle stability of the battery.

[0003] MXene is an emerging two-dimensional layered material with unique physical and chemical properties and good conductivity. Its structure is similar to graphite and has shown great application potential in the field of lithium-ion battery negative electrode materials. The SEM image is as follows: Figure 1 However, the negative electrode materials of sodium ion batteries have high requirements for negative electrode materials. The characteristics of ion radius larger than lithium ions make it impossible to directly apply either graphite or MXene, because MXene material sheets are prone to stacking, resulting in obstruction of ion transmission channels, affecting the battery's rate performance and cycle stability. At the same time, MXene materials have high surface energy and are prone to side reactions with electrolytes, further affecting the battery's cycle life and safety. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a polyacrylonitrile-based activated carbon fiber and a preparation method and application thereof. The preparation process of the present invention is simple, the production cycle is short, the cost is low, and the prepared polyacrylonitrile-based activated carbon fiber is uniform and has a smooth surface. When used in combination with MXene materials, it can effectively improve the stability of the layered structure of the MXene material, thereby improving the rate performance and cycle stability of sodium ion batteries.

[0005] The technical solution of the present invention is achieved in this way: A method for preparing polyacrylonitrile-based activated carbon fibers comprises the following steps: Step 1: crush polyacrylonitrile to 140-200 mesh, immerse in 5-15 mM phosphoric acid solution, and then treat with ultrasound for 10-20 min to obtain polyacrylonitrile flocs; Step 2: Under the protection of an inert atmosphere, the polyacrylonitrile flocs in step 1 are placed in a microwave tube furnace and activated at a high temperature of 400-600° C. for 10-30 min; Step 3: After the high-temperature activation is completed, the polyacrylonitrile-based activated carbon fiber is obtained by multiple air bath washing and finally vacuum drying.

[0006] Furthermore, during ultrasonic treatment, the power is 100~300W.

[0007] Furthermore, in step 2, the high temperature activation temperature is 450-550°C. Studies have shown that when high temperature activation is performed at 450-550°C, the carbonization effect of the obtained polyacrylonitrile-based active fiber is better, the excellent fiber morphology is maintained, the aspect ratio is consistent, and the polyacrylonitrile-based active fiber structure is dispersed without agglomeration. In particular, when high temperature activation is performed at 500°C, the carbonization effect of the obtained polyacrylonitrile-based active fiber is the best.

[0008] Furthermore, in step 3, during vacuum drying, the vacuum degree is 0.005~0.01MPa.

[0009] The above-mentioned polyacrylonitrile-based activated carbon fiber is used in sodium ion negative electrode materials.

[0010] Furthermore, polyacrylonitrile-based activated carbon fibers, MXene materials, conductive carbon black and PVDF are mixed and coated to prepare electrodes, and then sodium-ion batteries are assembled, wherein the mass ratio of polyacrylonitrile-based activated carbon fibers, MXene materials, conductive carbon black and PVDF is 2~3:4~5:2:1.

[0011] Furthermore, the mass ratio of polyacrylonitrile-based activated carbon fiber, MXene material, conductive carbon black and PVDF is 1:6:2:1.

[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses polyacrylonitrile with low synthesis cost as raw material to prepare activated carbon fiber, which can effectively reduce production cost. At the same time, low-concentration and stable phosphoric acid solution is used as impurity pretreatment agent. Phosphoric acid has strong water absorption, and phosphate ions have strong binding characteristics with organic matter, which can effectively remove impurity organic matter in polyacrylonitrile raw material. At the same time, ultrasonic treatment is adopted, which can utilize the strong penetration and energy concentration of ultrasonic waves to make phosphoric acid solution more effectively penetrate into the interior of polyacrylonitrile, accelerate the removal of impurities, and shorten the impregnation time; at the same time, microwave heating is used to achieve good environmental and energy benefits. Benefit. In addition, the entire reaction process is carried out under the protection of an inert atmosphere, which can effectively reduce the oxidation loss of materials and further improve the yield of activated carbon fiber. The yield of activated carbon fiber of the present invention can reach 89%.

[0013] 2. The polyacrylonitrile-based activated carbon fibers prepared by the present invention are uniform and structurally complete. By grinding, the polyacrylonitrile-based activated carbon fibers are mixed with two-dimensional layered MXene in the form of slurry, so that the polyacrylonitrile-based activated carbon fibers are embedded in the MXene material in the form of a spinning line to adjust the interlayer spacing, thereby ensuring that the sodium ion battery has good electrochemical performance. As the main body of the two-dimensional layered structure, the MXene material has a large interlayer spacing and excellent electrical conductivity. The addition of polyacrylonitrile-based activated carbon fibers not only increases the specific capacity and cycle stability of the negative electrode material, but also designs an appropriate two-dimensional layered structure for it, which is conducive to the stable embedding and deintercalation of sodium ions during the charging and discharging process.

[0014] In addition, by optimizing the ratio of activated carbon fiber and MXene materials, the electrochemical properties of the negative electrode material can be further regulated, thereby meeting the preparation of sodium ion batteries with different performance requirements. The construction of this new type of negative electrode material provides new ideas and directions for the development of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 -SEM image of MXene material.

[0016] Figure 2 -SEM image of the polyacrylonitrile-based activated carbon fiber prepared in Example 1, magnified 500 times.

[0017] Figure 3 -SEM images of the polyacrylonitrile-based activated carbon fibers prepared in Example 1, Example 4 and Example 5, magnified 50 times.

[0018] Figure 4 -IR graphs of the polyacrylonitrile-based activated carbon fibers prepared in Example 1 and Example 4.

[0019] Figure 5 -Rate cycle diagram of the assembled sodium-ion full battery.

[0020] Figure 6 -Charge and discharge curves of PAMX-0 (a) and PAMX-3 (b) negative electrode materials.

[0021] Figure 7 -Impedance diagrams of the assembled sodium-ion full cells PAMX-0 and PAMX-3. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0023] The scanning electron microscope used in the following examples is Sigma300 (manufactured by Carl Zeiss Microscopy Limited), the integrated constant temperature battery test box is MIHW-200-160CH (manufactured by Shenzhen Xinwell Electronics Co., Ltd.), the ultrasonic crusher is ZOLLO-650Y (Shanghai Zuole Instrument Co., Ltd.), and the experimental water is distilled water.

[0024] Example 1 A method for preparing polyacrylonitrile-based activated carbon fibers comprises the following steps: (1) crushing polyacrylonitrile into 180 mesh, and then immersing it in a 10 mM dilute phosphoric acid solution and ultrasonically treating it for 20 min to obtain polyacrylonitrile flocs; during the ultrasonic treatment, the power was 100 W; (2) Under inert atmosphere protection (flow rate of 0.05 m 3 / h), weigh 5g of polyacrylonitrile flocs and put them into a microwave tube furnace for high-temperature activation, set the temperature to 500℃, and the activation time to 20min; (3) After activation, the carbon fiber is cooled and then placed in a water vapor circulation system for multiple gas bath washing to remove phosphoric acid. The carbon fiber is then vacuum dried in a vacuum box at a vacuum degree of 0.005 MPa to obtain polyacrylonitrile-based activated carbon fibers.

[0025] Example 2 This embodiment is the same as embodiment 1, except that in this embodiment, the temperature during high temperature activation is 450°C.

[0026] Example 3 This embodiment is the same as embodiment 1, except that during high temperature activation in this embodiment, the temperature is 550°C.

[0027] Example 4 This embodiment is the same as embodiment 1, except that, during high temperature activation in this embodiment, the temperature is 400°C.

[0028] Example 5 This embodiment is the same as the embodiment 1, except that, during high temperature activation in this embodiment, the temperature is 600°C.

[0029] 1. The yield of polyacrylonitrile-based activated carbon fibers in Example 1 is 89% (yield = mass of polyacrylonitrile-based activated carbon fibers / mass of polyacrylonitrile flocs added to the microwave tube furnace × 100%). The polyacrylonitrile-based activated carbon fibers prepared in Examples 1 to 3 have the same aspect ratio and are dispersed in structure without agglomeration. The SEM image of the polyacrylonitrile-based activated carbon fibers prepared in Example 1, magnified 500 times, is shown in FIG. Figure 2 As shown by Figure 2 It can be seen that the aspect ratio of polyacrylonitrile-based activated carbon fibers is consistent and the structure is complete, indicating that the internal structure of the polyacrylonitrile-based activated carbon fibers is completely transformed at this temperature.

[0030] The SEM images of the polyacrylonitrile-based activated carbon fibers obtained in Example 1, Example 4 and Example 5, which were magnified 50 times, are shown in FIG. Figure 3 As shown in (a), (b), and (c), Figure 3 It can be seen that the carbonization effect of polyacrylonitrile-based active fibers at 500°C is the best, maintaining excellent fiber morphology and consistent aspect ratio; the carbonization of polyacrylonitrile-based active fibers at 400°C is incomplete, and some fibers form agglomerates; at 600°C, the carbonization of polyacrylonitrile-based active fibers is excessive, resulting in fiber bending and different sizes.

[0031] 2. The IR graphs of the polyacrylonitrile-based activated carbon fibers obtained in Example 1 and Example 4 are as follows: Figure 4 As shown, the red line corresponds to Example 1, and the black line corresponds to Example 4. It can be seen from the figure that after high temperature treatment, the infrared spectrum at 2354 cm -1 There is an obvious absorption peak of cyano (C≡N), 1685 cm -1 The stretching vibration peaks of C=C and C=N are at 1260 cm -1 The vibration peak of COH structure is at 1260 cm. As the temperature increases, the absorption peak of cyano structure of polyacrylonitrile decreases and almost disappears at 500℃. -1 After carbonization at 600℃, the carbon-based planar structure content is relatively large, and there is no obvious absorption peak in the spectrum.

[0032] 3. The polyacrylonitrile-based activated carbon fiber and MXene material, conductive carbon black, and PVDF prepared in Example 1 were mixed and coated to prepare electrodes, and a sodium ion full battery was assembled for rate cycle testing, wherein the mass ratio of polyacrylonitrile-based activated carbon fiber, MXene material, conductive carbon black, and PVDF was 0:7:2:1 (recorded as PAMX-0), 1:6:2:1 (recorded as PAMX-3), 2:5:2:1 (recorded as PAMX-4), 3:4:2:1 (recorded as PAMX-1), and 3.5:3.5:2:1 (recorded as PAMX-2). Specifically, the raw materials were mixed according to the above proportions, and an appropriate amount of N-methylpyrrolidone was added for grinding until a black and shiny slurry without obvious particles was formed. Copper foil was selected as the current collector for coating, and cut into pieces with a diameter of 15 mm after drying. When assembling the battery, Prussian blue NaFe 4 [Fe(CN) 6 ] 3 As the positive electrode material, a CR2025 sodium-ion full battery was assembled and tested in the order of positive electrode shell, gasket, positive electrode material, separator, negative electrode material, gasket, and negative electrode shell.

[0033] The results of the rate cycle test are as follows: Figure 5 As shown in the figure, it can be seen that the performance of PAMX-3 and PAMX-4 assembled batteries is better, and the initial capacity at a current density of 0.1A / g reaches 452 mAh / g and 473 mAh / g respectively. In contrast, when the PAMX-0 group without adding polyacrylonitrile-based activated carbon fiber has an initial capacity of only 207 mAh / g at a current density of 0.1A / g, indicating that polyacrylonitrile-based activated carbon fiber does play a role in improving battery performance. At the same time, when the current density increases to 1 A / g, the reversible capacity of PAMX-0 is 2.9 mAh / g, while the capacity of PAMX-3 and PAMX-4 groups is 14.9 Ah / g and 8.1 Ah / g, and the rate performance is significantly increased compared to PAMX-0. Regardless of whether it is a large current or a small current, its charge and discharge capacity mainly depends on the electron transmission efficiency and ion transmission capacity of the material. MXene is composed of MAX-Ti 3 AlC 2 The MXene anode exhibits poor rate performance after HF etching to remove Al. However, as the cycle progresses, its accordion-like structure becomes unstable, and the ion transmission capacity also decreases. The PAMX-3 and PAMX-4 anode materials have significantly improved rate performance due to the dispersion of polyacrylonitrile-based activated carbon fibers. However, the polyacrylonitrile-based activated carbon fibers do not have enough ion transmission channels. Therefore, when too much polyacrylonitrile-based activated carbon fibers are added to the PAMX-1 group of anode materials, its rate performance is poor.

[0034] To further study the structural stability of PAMX-3, PAMX-0 was used as a control, the two were combined into a battery, and the charge and discharge cycle test was carried out at a current density of 0.2 A / g. Figure 6 -a It can be seen that the first charge and discharge specific capacity of PAMX-0 reached 5 / 24mAh / g, and the second to fifth times showed obvious attenuation compared with the first time. This is because although the MXene material has a rich three-dimensional accordion-like structure and can provide a large number of sodium ion transmission channels, its structure is unstable when immersed in electrolyte and during the charge and discharge process. Figure 6 -b The charge and discharge curve of PAMX-3 shows that its first cycle charge and discharge curve capacity reaches 60 / 154mAh / g. Although the specific capacity decreases in the following charge and discharge process, it is still larger than that of PAMX-0, and it is relatively stable in the subsequent charge and discharge process, and the specific capacity does not fluctuate too much, indicating that the addition of polyacrylonitrile-based activated carbon fibers increases the structural stability of MXene, allowing it to have a larger specific capacity and higher activity during the charge and discharge process. Embedding polyacrylonitrile-based activated carbon fibers does increase the material's ability to store sodium capacitively, which can inhibit the formation of SEI film and slow down the deactivation process of the material.

[0035] At the same time, the impedance diagrams of PAMX-0 and PAMX-3 are as follows Figure 7 As shown in the figure, the obtained is a typical Nyquist curve, and the spectrum is composed of a semicircle in the high-frequency region and a small arc micro-curve in the low-frequency region. It can be seen from the figure that the slope of the low-frequency region of the PAMX-3 electrode with the addition of polyacrylonitrile-based activated carbon fiber is larger than that of the PAMX-0 without the addition of activated carbon fiber, indicating that there is a capacitive behavior; and from the high-frequency region magnification in the figure, it can be seen that the semicircle diameter of the high-frequency region of the electrode with the addition of polyacrylonitrile-based activated carbon fiber is smaller, indicating that the addition of polyacrylonitrile-based activated carbon fiber improves the performance of MXene and makes the electrode charge transfer impedance relatively smaller.

[0036] Finally, it should be noted that the above embodiments of the present invention are only examples for illustrating the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing polyacrylonitrile-based activated carbon fibers, characterized in that: The specific steps include: Step 1: crush polyacrylonitrile to 140-200 mesh, immerse in 5-15 mM phosphoric acid solution, and then treat with ultrasound for 10-20 min to obtain polyacrylonitrile flocs; Step 2: Under the protection of an inert atmosphere, the polyacrylonitrile flocs in step 1 are placed in a microwave tube furnace and activated at a high temperature of 400-600° C. for 10-30 min; Step 3: After the high-temperature activation is completed, the polyacrylonitrile-based activated carbon fiber is obtained by multiple air bath washing and finally vacuum drying.

2. The method for preparing a polyacrylonitrile-based activated carbon fiber according to claim 1, characterized in that: During ultrasonic treatment, the power is 100~300W.

3. The method for preparing a polyacrylonitrile-based activated carbon fiber according to claim 1, characterized in that: In step 2, the high temperature activation temperature is 450~550℃.

4. The method for preparing a polyacrylonitrile-based activated carbon fiber according to claim 3, characterized in that: The high temperature activation temperature in step 2 is 500°C.

5. The method for preparing a polyacrylonitrile-based activated carbon fiber according to claim 1, characterized in that: In step 3, during vacuum drying, the vacuum degree is 0.005~0.01MPa.

6. A polyacrylonitrile-based activated carbon fiber, characterized in that: The carbon fiber is prepared by the method for preparing a polyacrylonitrile-based activated carbon fiber according to any one of claims 1 to 5.

7. Use of the polyacrylonitrile-based activated carbon fiber described in claim 6 in sodium ion negative electrode materials.

8. The use of a polyacrylonitrile-based activated carbon fiber according to claim 7, characterized in that: Polyacrylonitrile-based activated carbon fibers, MXene materials, conductive carbon black and PVDF are mixed and coated to prepare electrodes, and then sodium-ion batteries are assembled, wherein the mass ratio of polyacrylonitrile-based activated carbon fibers, MXene materials, conductive carbon black and PVDF is 1~2:5~6:2:

1.

9. The use of a polyacrylonitrile-based activated carbon fiber according to claim 8, characterized in that: The mass ratio of polyacrylonitrile-based activated carbon fiber, MXene material, conductive carbon black and PVDF is 1:6:2:1.

Citation Information

Patent Citations

  • High oil-absorbing polyacrylonitrile hollow activated carbon fiber and preparation method thereof

    CN105544019A

  • Manufacturing method of carbon-based carbon dioxide adsorbents

    KR1020150064978A

  • Methods for manufacturing activated carbon fiber products

    TW200811325A